Garbhagriha of the Sadashiva Temple - Temples of India Project Team (Jio Institute, 2024)
The garbhagriha (sanctum sanctorum) is a small chamber where a large bust of Sadashiva or Maheshamurti is installed. The bust depicts three faces. The frontal face is of Tatpurusha, which is completely rubbed off. On the proper right, Aghora is portrayed, representing the aggressive aspect, while the left face is Vamadeva, reflecting the feminine aspect. The Aghora face wears a jatamukuta (a crown of matted hair) adorned with skulls and snakes. He has raised, arched eyebrows, large bulging eyes, and a third eye on the forehead. The deity is depicted with fangs, but one can notice the smile on its face, and holding a snake in his hand. The right half of Vamadeva’s face is also chipped off. The deity is shown with a jatamukuta featuring kirtimukhas (face of glory) and rounded curls. The deity has bow-shaped eyebrows, beautiful eyes, and a third eye on the forehead.